A comparison of linear and daily undulating periodized programs with equated volume and intensity for local muscular endurance - Rhea, M. R.; Phillips, W. T.; Burkett, L. N.; Stone, W. J.; Ball, S. D.; Alvar, B. A.; Thomas, A. B. (The Journal of Strength and Conditioning Research, 2003)
The purpose of this study was to compare linear periodization (LP), daily undulating periodization (DUP), and reverse linear periodization (RLP) for gains in local muscular endurance and strength. Sixty subjects (30 men, 30 women) were randomly assigned to LP, DUP, or RLP groups. Maximal repetitions at 50% of the subject's body weight were recorded for leg extensions as a pretest, midtest, and posttest. Training involved 3 sets (leg extensions) 2 days per week. The LP group performed sets of 25 repetition maximum (RM), 20RM, and 15RM changing every 5 weeks. The RLP group progressed in reverse order (15RM, 20RM, 25RM), changing every 5 weeks. The DUP group adjusted training variables between each workout (25RM, 20RM, 15RM repeated for the 15 weeks). Volume and intensity were equated for each training program. No significant differences were measured in endurance gains between groups (RLP = 73%, LP = 56%, DUP = 55%; p = 0.58). But effect sizes (ES) demonstrated that the RLP treatment (ES = 0.27) was more effective than the LP treatment (control) and the DUP treatment (ES = 0.02) at increasing muscular endurance. Therefore, it was concluded that making gradual increases in volume and gradual decreases in intensity was the most effective program for increasing muscular endurance.